Acehnese's Digital Literacy Skills in Verification News from Social Media - Fizzy Andriani; Eni Kardi Wiyati; Dwi Ajeng Widarini; Muhammad Saifulloh (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
Communication technology has recently become a new medium where society can choose information and the media they want to consume. The media can still influence their minds. Based on the National Survey of Internet User Penetration Data, in March 2019, by APJII (Internet Service Provider Association), the  internet penetration  rate in Aceh was recorded at 64.40% who accessed the internet. This research aims to find Acehnese's Digital Literacy Skills in Verification News from Social Media. The data collection method  used for  this study is  a questionnaire instrument via Google Form to people in Nanggroe Aceh Darussalam (NAD) province. Meanwhile, secondary data was collected through literature studies and previous research. The result shows that the people of Aceh, especially millennials and Generation Z, have enough  digital literacy skills  to access  digital media, understand content, and verify news.